2018
DOI: 10.29354/diag/81692
|View full text |Cite
|
Sign up to set email alerts
|

Chatter detection using principal component analysis in cold rolling mill

Abstract: Most cold rolling mills are prone to chatter problem. Chatter marks are often observed on the strip surface in cold rolling mill leading to downgrade and rejection of rolled material. Chatter impact product quality as well as productivity of mill. In absence of online chatter detection no corrective action can be taken immediately and whole campaign gets affected. Most conventional approach for online chatter detection is by using vibration measurement of mill stands in time & frequency domain. Present work pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Анализ спектра ограничен диапазоном частот от 0 до 1300 Гц. Автоколебания появляются на пятой клети на полосах толщиной меньше 1 мм и скоростях прокатки выше 20 м/с [23].…”
Section: Introductionunclassified
“…Анализ спектра ограничен диапазоном частот от 0 до 1300 Гц. Автоколебания появляются на пятой клети на полосах толщиной меньше 1 мм и скоростях прокатки выше 20 м/с [23].…”
Section: Introductionunclassified
“…In Haoran et al (2011), a computer simulation analysis was presented by an ANSYS finite element harmonic response analysis module and the conclusion was obtained that the tensional vibration and axial vibration will cause the phenomenon of coupling vibration under certain conditions. In Maria and Susanna (2013), a kind of hysteretic nonlinear vertical vibration dynamic model which considers hysteresis of strip's plastic deformation was established. In Skripalenko et al (2011), chatter in food processing rolling mills was the undesirable vibration observed in most of the food processing rolling mills operating at high speed and rolling thin strip.…”
Section: Introductionmentioning
confidence: 99%